Microstrip Patch Rectangular Susunan Side By Side Multielemen Pada Frekuensi 2.4 Ghz Berbasis Silver Nanowires (Agnws) - M Reza Hidayat; Irfan Noor Muhammad; Sofyan Basuki (Department of Electrical Engineering, UNJANI, 2022)
In this study, the design uses three variations for silver nanowires and three variations of patches. Variations of silver nanowires are in the form of length, diameter and number of silver nanowires, while for patches, variations of single patch, double patch and triple patch are used. The microstip antenna uses a patch specification with a thickness of 0.035 mm made of copper, with a density of 1.6 mm for a substrate made of FR-4 epoxy. Based on the observations of the antenna parameters from the characteristics of the silver nanowires variation, the desired results were obtained at variations in diameter of 300 nm, length of 32 mm and the number of 342 silver nanowires in triple patch with return loss = -20,731 dB; VSWR = 1.202; gain = 5,338 dB and directivity = 9,970 dBi. The above results have increased the desired value compared to triple patch microstrip antennas without nanowires with a return loss value = - 16,191 dB; VSWR = 1.366; gain = 5.142 dB and directivity = 9.829 dBi.